Methodological individualism as opposed to methodological holism. History, relevancy and the implications of the (insoluble?) debate on the explanatory capacity and scientific status of sociocultural anthropology - Nina Kulenović (University of Belgrade, 2016)
The paper is part of wider research into the status of explanation in the debate on the scientific status of anthropology – wherein one of the key assumptions is that there is a strong correlation between theoretical and methodological structures which would make them inseparable, and that explanation or explanatory potential, is the point of convergence which can be used to test for the possibility of separating theoretical and methodological structures in the first place. To test this idea, a line of debate between methodological holism and methodological individualism – one of the longest running and most complex debates in the social sciences and humanities – was considered. The historical background of the debate has been highlighted, and its relevancy and implications in the controversy about the explanatory capacity and scientific status of sociocultural anthropology.